Value characteristics of land resources and ways of their implementation in the economac turnover - Stetsyuk, M.; Nahorna, L. (Land Management, Cadastre and Land Monitoring, 2017)
Land resources are among the priority in sustainable development of the State as a whole and its administrative divisions in particular.Their substantial involvement and integration in most areas of operation, positioning as a factor of productive forces and significant for the sustenance of the population provide an opportunity to consider these unique resources and key to the country.The current situation in Ukraine revealed that land resources are gradually drawn into the economic turnover. In such circumstances, the land resources acquired traits and abilities to generate market value. They have gradually become involved in the activities of the individual sectors of the economy and contribute significantly to the development of business processes. Thus, the extensive use of monetary signs associated with new, innovative approaches.As experience shows, the most common today is the conversion mechanism of land resources in the capital believe the activities of the trust funds and securitization, which should be based on reliable data for the integrated assessment of land resources. In General, the methods of these procedures are evolving, so it is advisable to use foreign experience. At the same time, it should be noted that to achieve an acceptable level of capitalization is possible thanks to the use of other regulatory instruments. In our view, it is appropriate to include certain additional funds (if we consider capitalization as a broader process).An important issue is the structure of formation of cost. So, the cost depends on the category of established and emerging processes that must be taken into account in the process of research the cost of signs of land resources.From a methodological point of view, the settled (ordinary) monetary signs land resources belongs to the normative score as basis for the definition of determining the value of land. Although this rating does not reflect the real market value of the land, even in regions with high rates. Many unique properties of Ukrainian land are simply ignored.The analysis of evaluation indicators nominal payments for the land in the Consolidated budget for the period 1999-2015. points to existing growing trend (with the exception of individual points the change of trend). In General, the existence of such processes shows positive trends, however, given the existing capacity, payments for the use of land resources could be much greater. The question is as to the formation of such payments and low current rates that are charged to users of land resources.It is not worth that a significant portion of the profits, which is formed in the APK, is generated by the export of grain. So there is the potential of raising fees for use of the resource.One of the tools for solving this problem can be considered in view of the potential signs of value are activated under the influence of new processes, namely: capitalization, corporatization, securitization, and the like.Land holds a special place in the structure of natural resource potential of the state. Identifying high cost performance, they are attractive for Ukrainian and foreign investors. In addition to ordinary usage, cost characteristics (especially those that are based on new processes) form favorable conditions for active use of the resource as environment to attract capital.Key words: land resources, cost characteristics, the implementation of the economic circulation.